2019
DOI: 10.1111/apa.14892
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of classroom physical activity breaks on children’s on‐task behaviour, academic achievement and cognition

Abstract: Aim This study examined the effects of different types of classroom physical activity breaks on children’s on‐task behaviour, academic achievement and cognition. Methods Participants were 87 Australian primary school students (mean age 9.11 ± 0.62 years), recruited from one school. Three classes were randomly assigned either to activity breaks only (n = 29), activity breaks and mathematics combined (n = 29), or control conditions involving only mathematical content (n = 29). Students were engaged in five minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
80
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 28 publications
7
80
1
3
Order By: Relevance
“…Physical activity seems to improve cognition, learning and eligibility for higher education, but the pathways are largely unknown. Some researchers have suggested that physical activity has direct positive effects on the brain and nervous system.…”
mentioning
confidence: 78%
See 4 more Smart Citations
“…Physical activity seems to improve cognition, learning and eligibility for higher education, but the pathways are largely unknown. Some researchers have suggested that physical activity has direct positive effects on the brain and nervous system.…”
mentioning
confidence: 78%
“…In this issue of Acta Paediatrica, Mavilidi et al report that short physical activity breaks during maths lessons enhanced the learning behaviour of children at a mean age of nine years . This is very interesting because large well‐educated populations are a prerequisite for successful modern societies.…”
mentioning
confidence: 99%
See 3 more Smart Citations